Establishing the association between ankylosing spondylitis and its comorbidities based on their shared pathways - Alhassan Usman Bello,; Sarahani Harun,; Nor Afiqah-Aleng,; Rajalingham Sakthiswary,; Zetiazura Mohamed-Hussein, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Ankylosing spondylitis (AS) is an autoimmune and inflammatory arthritis associated with various comorbidities, such as axial spondyloarthritis (axSpA), cardiovascular disease (CD), Guillain-Barre syndrome (GBS), rheumatic fever (RF), and vasculitis (Vs). The co-occurrence of these comorbidities underlies the molecular mechanisms of complex biological interactions shared by dysfunctional pathways. We used network biology and computational methods to establish association between biological processes and molecular mechanisms in AS and its comorbidities. The findings showed significant association between twelve shared pathways in AS and its comorbidities. These shared pathways are associated with pathobiological processes, such as immune responses, inflammatory responses and cellular signaling responses, in AS and its comorbidities. Nine of these pathways are involved in signaling, two are involved in the metabolic processes, and one is involved in the regulatory processes in AS and its comorbidities. In conclusion, this work highlights specific and common shared pathways in AS and its comorbidities. These findings provide information on key shared pathways that can be used to explain the pathobiological processes of AS and its comorbidities and can help in therapeutic discovery towards accurate diagnosis and effective treatment.